Islamic Education Marketing Management Promotional Efforts for Prospective New Students: A Literature Study - Indah Ummis Sholehah; Hilmi Qosim Mubah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Marketing management of Islamic education is a determinant of the quantity of prospective students who will enroll in an Islamic education institution. Marketing management is really needed so that Islamic education can achieve the target quantity of prospective students in the future. Promotional activities through educational marketing management is a solution that can be used by the unit. Islamic educational institutions in offering, introducing and influencing prospective new students to join and become part of the education itself. The aim of this research is to find out how educational management and marketing are in an effort to promote educational institutions to prospective new students. This research uses the library research method by going through a reading process, recording important data that is appropriate to the context being studied. The primary source for this research is a study of Islamic education marketing management, while the secondary data is supporting studies that are relevant to the research context. The results of this research are: 1) The steps used are management methods, including planning, organizing, mobilizing and supervising in order to carry out institutional promotion. 2) The strategy to promote Islamic educational institutions is to use print and non-print media such as socialization agendas for the community or education below, banner information media, social media and pamphlet information media.